Effects of N/Z on survival probability of heavy nuclei - 叶巍 杨宏伟 (Chinese physics C, 2008)
The excitation functions of the evaporation residue formation probability of three heavy nuclei ^194pb, ^200Pb and ^206pb are calculated by using a Langevin equation coupled with a statistical decay model. The results show that the neutron-to-proton ratio （N/Z） of a compound nucleus has an effect on survival probability and this effect becomes larger with increasing N/Z. This is because the fission barrier and the pre-saddle particle emission depend on the N/Z ratio of the system.